(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Peptic ulcer of the stomach and duodenum is one of the most common pathologies of the digestive organs. According to WHO data, more than 4 million new cases are registered annually in the world, and the frequency of relapses within a year reaches 40-60%. Despite the widespread implementation of Helicobacter pylori eradication therapy, morbidity rates remain high, indicating a multifactorial nature of the pathogenesis. In addition to H. pylori infection and the aggressive effects of gastric juice, psycho-emotional factors play an important role: chronic stress, depressive and anxiety disorders, sleep disturbances, as well as the imbalance of the sympathetic and parasympathetic nervous systems. These factors can enhance the secretion of hydrochloric acid, disrupt mucosal trophic processes, and slow down reparation processes.